Design and Development of Organic Electrocatalysts for CO2 Reduction - Altemani, Fatin (2025)
The electrochemical carbon dioxide reduction reaction (CO2RR) represents a promising method for converting carbon waste streams into valuable chemicals. Current CO2RR electrocatalysts often rely on expensive and rare platinum group metals, highlighting the need for more sustainable and cost-effective alternatives. This thesis explores the use of aromatic nitro group-bearing catalysts for the CO2RR, focusing on their performance in different electrolyte systems. Cyclic voltammetry was employed to evaluate catalytic efficiency. Additionally, the influence of the electrolyte and gas environment (N2 vs. CO2) on the catalytic activity was investigated. Results demonstrated that aromatic nitro group catalysts exhibited improved CO2 reduction activity in both electrolyte systems. This study provides insights into the relationship between catalyst structure, electrolyte composition, and gas environment, suggesting that further optimization of these catalyst-electrolyte systems could enhance the efficiency and selectivity of the CO2RR, advancing sustainable chemical production processes.